Experimental research on the miscibility law of methanol-product oil blending systems - Shangxin ZHAO; Guiliang PANG; Shujuan QIU; Xin HUANG; Lin TENG (You-qi chuyun)
Objective As an emerging energy source, methanol plays a crucial role in the energy transition. Implementing sequential transportation of methanol through existing product oil pipelines can lower transportation costs and enhance efficiency in the transportation process. Nevertheless, the specific miscibility of methanol with gasoline and diesel significantly influences this transmission process. Methods Experimental research was carried out using a setup independently designed and established for blending methanol with product oils, with a focus on determining phase separation temperatures in methanol-product oil blending systems at different methanol-to-oil ratios and varying water contents. Results (1) Anhydrous methanol exhibited complete miscibility with gasoline within the temperature range of － 10 to 50 ℃. (2) In water-containing methanol-gasoline blends, the hydrogen bonds formed by water and methanol molecules were significantly stronger than the binding forces between methanol and gasoline. Even a small amount of water could decrease the miscibility between methanol and gasoline. For every 0.2% increase in water content in methanol, the phase separation temperature increased by 7 to 8 ℃. As the methanol-oil ratio increased, the phase separation temperature of water-containing methanol and gasoline initially rose before decreasing, reaching its peak at a water-containing methanol volume fraction of 40%. (3) A clear stratification was observed between anhydrous methanol and diesel. With rising temperatures, the solubility of diesel in methanol increased. (4) Water-containing methanol was found to be incompletely miscible with diesel. As the water content increased, the separation of methanol from diesel became more pronounced. (5) As temperatures decreased, the miscibility between methanol and product oils reduced, resulting in droplet separation at the bottom of the blending systems. These droplets then ascended gradually due to buoyancy forces. Conclusion The research results clarified the influence of miscibility in methanol-product oil blending systems under various conditions and unveiled the evolution of stratification in these systems as temperatures decrease. These findings offer a scientific foundation and data support for designing and operating the sequential transportation process of methanol in product oil pipelines.